Improvement a positive attitude towards abstract algebra through APOS theory approach. (July 2020) - Arnawa, I M; Yanita; Ginting, B; Yerizon; Nita, S
Abstract: Rate of students' participation in teaching and learning Abstract Algebra (AA) depends upon attitude towards AA and Students' success in AA depends upon rate of students' participation in teaching and learning of AA. Thus it is very important to improve students' attitude towards AA. This research was pre-experimental one shot case study design. The subject of this study were 50 students who participating in the AA course academic year 2018/2019 at Andalas University. A questionnaire was used to examine student's attitudes towards AA and its learning. Descriptive statistics and t-test with level of significance α = 0.05 were used for data analysis. The results showed that: (1) APOS theory approach can improve students attitude towards AA and its learning (2) There was no a gender gap in students' attitude towards AA and its learning. (3). There was a positive correlation between attitude towards AA and its learning.